2003
DOI: 10.1002/nbm.797
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing metabolic changes in breast‐cancer tissue using 1H‐NMR spectroscopy and self‐organizing maps

Abstract: In-vitro NMR spectroscopic examinations of tissue extracts can be combined with appropriate pattern-recognition and visualization techniques in order to monitor characteristic metabolic differences between tissue classes. In the present study, such techniques are applied to a set of 88 breast-tissue samples with the intention of identifying typical differences between various tissue classes. The set contains 49 breast-tumor samples of various tumor grades and 39 samples of healthy tissue. The metabolite compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 29 publications
11
106
0
1
Order By: Relevance
“…In line with these studies, increased levels of cholesteryl esters in glioma tissues and in surrounding infi ltrated areas of human brain have been reported compared with normal material while cholesterol was signifi cantly lower in tumor tissue ( 43 ), suggesting a possible involvement of cholesteryl esters in the development and progression of these tumors that remain untreatable. In addition, important amounts of cholesteryl esters were detected only in tumor lesions at the highest grade of malignancy in cerebral, renal, and prostatic neoplastic tissues, further supporting the concept that they may participate in the aggressivity and progression of different tumors ( 31,(44)(45)(46)(47). In accordance with these different studies, the role of cholesteryl esters in cell proliferation and invasion was further demonstrated by culturing the nontumor cells expressing the wild-type CCK2R in the presence of cholesteryl oleate.…”
Section: Inhibition Of Cholesteryl Ester Formed Through the Activatiomentioning
confidence: 59%
“…In line with these studies, increased levels of cholesteryl esters in glioma tissues and in surrounding infi ltrated areas of human brain have been reported compared with normal material while cholesterol was signifi cantly lower in tumor tissue ( 43 ), suggesting a possible involvement of cholesteryl esters in the development and progression of these tumors that remain untreatable. In addition, important amounts of cholesteryl esters were detected only in tumor lesions at the highest grade of malignancy in cerebral, renal, and prostatic neoplastic tissues, further supporting the concept that they may participate in the aggressivity and progression of different tumors ( 31,(44)(45)(46)(47). In accordance with these different studies, the role of cholesteryl esters in cell proliferation and invasion was further demonstrated by culturing the nontumor cells expressing the wild-type CCK2R in the presence of cholesteryl oleate.…”
Section: Inhibition Of Cholesteryl Ester Formed Through the Activatiomentioning
confidence: 59%
“…Similarly, PLS-DA has been previously used for the analysis of metabolic changes (16). Currently, NMR-based metabolomics is applied in several fields, including the study of plants (17)(18)(19), blood plasma (20,21), urine (22) and cancer (23)(24)(25)(26). In the present study, carboplatin (CBP) and pingyangmycin (PYM) were used to induce MDR of the oral squamous cell line, Tca8113, by applying an increasing concentration for a period of six months.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rodent mammary tumors have high levels of intracellular taurine [13]. Furthermore, Beckonert et al [14] have shown that the intracellular concentration of taurine, measured by NMR spectroscopy, is increased in breast tumours compared with that found in healthy breast tissue. Indeed, it has been suggested that the intracellular concentration of taurine may be a potential indicator of tumour aggressiveness [15].…”
Section: Introductionmentioning
confidence: 99%